MULTIFUNCTIONAL MODIFIED CARBON FOR PURIFICATION OF GROUNDWATER - Dmitry E. Propolsky; Valentin I. Romanovski (Водное хозяйство России: проблемы, технологии, управление)
Increased iron content in water has a detrimental effect on human health and leads to overgrowth of water supply networks, and an increased bacterial groundwater index causes microbial contamination of drinking water. In this regard, the urgent issue is the creation of modified multifunctional filtering materials. A modified material based on activated carbon coated with nanostructured iron and zinc oxides was obtained in order to deferrization of groundwater and prevent biofouling. As a modification method, the method of solution combustion synthesis was used. The surface morphology, chemical and phase composition of the coatings were studied. It has been shown that the effectiveness of deferrization of groundwater is almost 3 fold higher when using modified carbons comparing to the initial activated carbon.